The influence of Pasak Bumi (Eurycoma longifolia Jack.) root infusa to male white mouse libido - Diana Itjin; Luciana Kuswibawati (Indonesian Journal of Pharmacy, 2004)
Pasak Bumi ( Eurycoma Longifolia Jack.) is one of forest plant which have been used as aphrodisiac for many generation by the people in hinterland Kalimantan. The study was aimed to gain information of influence of pasak bumi root infusa to male white mouse libido.The research was pure experimental applying completely randomized design. Sixteen male white mice was divided into 2 groups which first group (negative control) was treated with aquadest by oral and the second group treated with pasak bumi roots infusa which its dosage 100 mg / 100 g body weight of male white mice by oral once a day for 21 days..Data of introduction, climbing, and coitus analysed with one way ANOVA and General Linear Measure model with 95% confidence level. The result indicated that usage period of pasak bumi root infusa (Eurycoma Longifolia Jack.) improving male white mice Iibido, which was showed by the increament amount of introduction and climbing of male white mice to female white mice.Key words: Eurycoma longifolia roots, libido, introduction, climbing, coitus